The Efficiency of Pesantren Cooperative using Data Envelopment Analysis (DEA): A Case in Indonesia - Mimma Maripatul Uula; Solihah Sari Rahayu (SMART Insight, 2022)
The purpose of this research is to analyze the level of efficiency of Islamic boarding schools cooperatives as well as potential improvements needed, and to compare the efficiency of Islamic boarding schools cooperatives. In addition, this research also looks at the efficiency of Islamic boarding school cooperatives during the Covid-19 pandemic. The research period used in this research is from 2014-2021 with a research sample of 2 Islamic boarding schools cooperatives. The analytical method used is a non-parametric approach, namely Data Envelopment Analysis (DEA), with secondary data sources originating from the financial reports of Islamic boarding schools cooperatives as the research sample. Furthermore, the input variables used are fixed assets, mandatory savings and principal savings. The output variable consists of SHU and deposits in other bodies. The results of this study indicate that the efficiency of Islamic boarding school cooperatives during the 2014-2021 period has fluctuated from year to year. Based on the level of efficiency, the Islamic boarding school cooperative B has a higher efficiency compared to the Islamic boarding school cooperative A. Then in the analysis of efficiency during the pandemic, the efficiency of the Islamic boarding school A cooperative tends to be relatively stable. Meanwhile, the pesantren B cooperative showed a significant increase in 2021, even though it experienced a decline in the 2020 period. And based on analysispotential improvement, the biggest cause of inefficiency in pesantren A cooperative comes from the input variable, namely SHU, and in pesantren B cooperative is fixed assets. This research also provides recommendations to cooperatives to further increase their efficiency, for regulators, it is expected to provide full support to Islamic boarding schools cooperatives, and for academics to update this research in line with research limitations.